Time pressure and the wellbeing of parents with young children in Australia - Johnson, Sarah E. (Curtin University, 2010)
Parental time pressure, in terms of actual workload and subjective reports, is high and likely to increase in the future, with ongoing implications for personal wellbeing. The combination of parenting young children and maternal employment, in particular, gives rise to greater time pressure in families. Although characterised by increasing diversity, two of the most time pressured family types, dual-earner and lone parent families are central features in the Australian demographic landscape. In view of predominant social and cultural trends, the ‘problem’ of time pressure is deep-rooted and set to grow. While the need to address ‘work-family balance’ is prominent in political and social life, the relationship between time pressure and wellbeing has not been well quantified and we know little about how that relationship works in families. At the heart of the time pressure problem, is a potential threat to the healthy development of children. This thesis, then, is broadly concerned with the nature of time pressure and its relationship with parental wellbeing when they are caring for young children.The central aim of the thesis is to determine whether time pressure has a significant impact on the self-reported wellbeing of parents with young children. There are four main research questions. Time pressure is defined as being both objective (‘parental time use’) and subjective in nature (‘parental perceptions about their time’). The questions are: (1) What is the relationship between parental time use and parental perceptions about their time? (2) How do parental time use and parental perceptions about their time relate to their self-reported wellbeing? (3) Are the effects of parental time use and parental perceptions about their time on self-reported wellbeing modified by other perceived stressors and psychological coping resources? (4) What are the predictors of self-perceived time pressure? Because of their broad scope, each of these questions is given further focus by the stating of specific sub-components.The study draws from several selected theoretical perspectives and models around the influence of time on individual health and wellbeing. Because the experience of time pressure has multiple interacting levels of influence from the individual through to family, work, and community settings and more widely from the social, political and cultural environment, the thesis is underpinned by ecological theory. To allow for the meaningful and practical measurement of time pressure within different contexts, the Family and Community Resource Framework was adopted. The Framework views time as a resource that can be utilized and traded by families with other resources of human, financial, psychological and social capital to enable family functioning and individual wellbeing. Then, to make sense of the pathways of influence, subjective time pressure was conceptualized as a psychosocial factor within an epidemiological model of the social determinants of health. These theoretical perspectives in combination are woven throughout the thesis as both a guide and a means of interpreting results.In addressing the broad research gaps around time pressure and parental wellbeing, the study took a population perspective and a quantitative methodological approach. A sub sample of parents with young children (at least one resident child aged less than six) was drawn from Wave Two of the Household Income and Labor Dynamics of Australia (HILDA) Study, conducted in 2002. Acknowledging the key role of gender and employment status in the experience of time pressure, all analysis was undertaken separately for employed mothers (n=451), non-employed mothers (n=512) and employed fathers (n=686). At another level that recognizes the influence of family structure and joint employment arrangements, analysis was undertaken for parents in ‘dual-earner families’ (n=346), ‘traditional families’ (n=321) and ‘lone mother families’ (n=145). This approach addressed the specific deficiency of quantitative studies of time pressure (objective and subjective) among families at the population level.The concepts of “parental wellbeing”, “parental time use”, and “parental perceptions about their time” were all operationalized by a set of self-reported measures. Parental wellbeing was captured by the mental health, vitality and general health subscales of the MOS-Short-Form 36 allowing for variation in positive health states. Parental time use (objective time pressure) was measured by their self-reported estimates of average weekly hours in paid work, household work (sum of indoor and outdoor activities, and chores) and of their time spent with children. Furthermore, these three estimates were summed to provide two measures of total workload. Parental time perceptions (subjective time pressure) were quantified by questions about their paid work hour preferences and satisfaction, perceived fairness in their share of housework and childcare, satisfaction with their amount of free time, and primarily by their self-perceived time pressure. The study also drew on indicators of job quality, financial wellbeing, parenting stress and perceived social support to examine the modifying role of other psychological resources on the relationship between time pressure and wellbeing. The bulk of analyses utilized multivariate linear regression techniques to examine the simultaneous effects of time use and parental perceptions about their time on mental health, general health and vitality, with adjustment for family characteristics and indicators of human and financial capital.Primarily, the thesis concludes that time pressure has a significant negative impact on the wellbeing of many Australian parents with young children, in particular, when they are employed. ‘Self-perceived time pressure’ proves to be a complex issue as high levels were associated with large amounts of paid work and household work; with perceptions of unfairness in household work and childcare; with low free time satisfaction; with higher levels of job and parenting stress, and lower levels of perceived social support. The thesis provides conclusive evidence that a high level of self-perceived time pressure lowers the mental health, vitality and general health of all parents. For employed parents, low levels of satisfaction with their paid work hours, and for all parents, low levels of satisfaction with their free time hours had an additional detrimental effect on their mental health and vitality. In contrast, there was little evidence overall that parental distribution of time to specific activities, or that a greater total workload independently contributed to lower wellbeing. Unpredictably, employed mothers had better wellbeing when they spent a relatively large amount of time with their children. Furthermore, a high level of self-perceived time pressure exerted a detrimental effect on the wellbeing of some employed parents even after adjustment for other reported stressors around work and family life. Additionally, there was evidence that among the most highly time pressured mothers a higher level of perceived social support did little to buffer the impact of time pressure on aspects of their wellbeing. Integral to the findings is the evidence that family employment arrangements and structure alter the meaning of time pressure and its relationship to parental wellbeing.These conclusions raise the question of how to avoid time-pressured circumstances in Australian families, and how to support and resource parents who are already feeling chronically pressed for time. The very nature of time pressure implies multiple levels and points of intervention at the policy, community, workplace, family and individual level. Avoiding time pressure in families requires continued policy directions aimed at creating flexibility and choice in how parents divide their time between work and family with safeguards against excessive hours in paid work. Furthermore, the findings prompt the need for an expanded policy to one that includes leisure or time for oneself and the facilitation of parental time with children. From a preventive perspective, specific and early intervention at a family level from pre-conception through to antenatal and early parenting programs will help to facilitate a gender equitable approach to the division of labour. Among employed parents, correlations between self-perceived time pressure and their perceived stress and complexity of paid work suggest a greater role for workplaces in preventing and identifying psychosocial stress among employees. Inherently more difficult is identifying and supporting parents who are already feeling the strain. The prevalence of perceived time pressures and the strong negative association with parental wellbeing suggests the need for a public health response. The urgency for action lays in the potential damage to the relationship between the parent and developing child. Fundamentally, all strategies should be aimed at giving parents back a sense of control over their time.The thesis lays a foundation for ongoing research examining the effects of paid and unpaid work patterns, free time and perceived time pressures on parental, child and family wellbeing over time.